?GRAFT COPOLYMERISATION OF ACRYLONITRILE ON TO POLYVINYL ALCOHOL - KHAN, A. RASHEED; HASAN, SHABlH-UL; IFRAHIM, A.F.K.; YOUSUFZAI, A.H.K. (Biological Sciences - PJSIR, 1995)
Acrylonitrile (AN) has been graft polymerised on to polyvinyl alcohol (PYA) in aqueous medium using potassium persulfate as an initiator.The grafting wascharacterisedby elemental analysis,solubility,I.R.and intrinsic viscosity measurements. The rate of conversion of monomer.rateof graftcopolymerisation (Rg), grafting ratio (GR) increased with increasing concentration of AN and decreased with increasing toncentration of PYA. Increase in catalytic concentration was foundtoincreaserateofconversionofmonomer RgandGr.SomePYAisleftunturned by growing polymer chain of PANwhich increases with increasing concentration of AN PYAor potassium persulfate. TheeffectsofconcentrationofAN. PYAandpotassiumpersulfateonGR.Rg,rateofconversionof monomerand PYA used in grafting (PG) were studied.